Microencapsulated phage composites with increased gastrointestinal stability for the oral treatment of Salmonella colonization in chicken - Zhang, Bo; Wang, Yongxia; Wang, Fangfang; Zhang, Yongying; Hao, He; Lv, Xingbang; Hao, Liuhang; Shi, Yuxiang (Frontiers in Veterinary Science, 2023)
Salmonella infection, one of the common epidemics in the livestock and poultry breeding industry, causes great economic losses worldwide. At present, antibiotics are the most commonly used treatment for Salmonella infection, but the widespread use of antibiotics has increased drug resistance to Salmonella. Phage therapy has gradually become an alternative method to control Salmonella infection. However, phage, a specific virus that can infect bacteria, has poor stability and is prone to inactivation during treatment. Microencapsulated phage microspheres can effectively solve this problem. Accordingly, in this study, Salmonella phages were microencapsulated, using the xanthan gum / sodium alginate / CaCl2 / chitooligosaccharides method, to improve their gastrointestinal stability. Furthermore, microencapsulated phages were evaluated for in vitro temperature and storage stability and in vivo therapeutic effect. Phage microspheres prepared with 1 g/100 mL xanthan gum, 2 g/100 mL sodium alginate, 2 g/100 mL CaCl2, and 0.6 g/100 mL chitooligosaccharides were regular in shape and stable in the temperature range of 10-30 ℃. Also, microencapsulated phages showed significantly improved stability in the simulated gastric juice environment than the free phages (p < 0.05). In the simulated intestinal fluid, microencapsulated phages were completely released after 4 h. Moreover, microencapsulated phages showed good storage stability at 4 ℃. In the in vivo experiments detecting Salmonella colonization in the intestinal tract of chicks, microencapsulated phages showed a better therapeutic effect than the free phages. In conclusion, microencapsulated phages exhibited significantly improved stability, gastric acid resistance, and thereby efficacy than the free phages. Microencapsulated phages can be potentially used as biological control agents against bacterial infections.